Building climate-resilient livelihoods for refugees and host communities in Jordan - Marianne, Gadeberg; Schapendonk, Frans; Jaskolski, Martina (2024)
The World Food Programme (WFP) has requested researchers from the CGIAR Research Initiative on Fragility, Conflict, and Migration (FCM) to investigate which financing options could enable refugees and host communities to invest in climate-resilient, sustainable livelihoods. The result is a series of research-backed recommendations set to inform future WFP projects.